2021
DOI: 10.3390/jcm10102172
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models to Predict 30-Day Mortality in Mechanically Ventilated Patients

Abstract: Previous scoring models, such as the Acute Physiologic Assessment and Chronic Health Evaluation II (APACHE II) score, do not adequately predict the mortality of patients receiving mechanical ventilation in the intensive care unit. Therefore, this study aimed to apply machine learning algorithms to improve the prediction accuracy for 30-day mortality of mechanically ventilated patients. The data of 16,940 mechanically ventilated patients were divided into the training-validation (83%, n = 13,988) and test (17%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Comparing MLTs in predicting hard outcomes in adult ICUs setting (e.g., in-hospital mortality) is under debate but remains under-addressed in the pediatric ICU environment. However, the results agree with the literature concerning the mortality outcome prediction via MLT models in the ICU setting [ 36 ]. For example, the gradient boosting (GB) model showed the highest ROC (0.79 (0.77–0.80)) for the 30-day mortality prediction in mechanically ventilated patients, followed by the random forest model (0.78 (0.76–0.80)).…”
Section: Discussionsupporting
confidence: 90%
“…Comparing MLTs in predicting hard outcomes in adult ICUs setting (e.g., in-hospital mortality) is under debate but remains under-addressed in the pediatric ICU environment. However, the results agree with the literature concerning the mortality outcome prediction via MLT models in the ICU setting [ 36 ]. For example, the gradient boosting (GB) model showed the highest ROC (0.79 (0.77–0.80)) for the 30-day mortality prediction in mechanically ventilated patients, followed by the random forest model (0.78 (0.76–0.80)).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we combined ML-based models with electronic medical record data to retrieve information on various clinical characteristics that affect in-hospital mortality, and we determined that the RF, XGB, and GBM models exhibited the most favorable discriminative ability with AUROCs of 0.816, 0.806, and 0.823, respectively. The accuracy of the ML models used in this study in predicting in-hospital mortality in the patients receiving CRRT is comparable to that reported in previous studies [ 7 , 10 , 22 , 23 , 24 , 25 ]. In particular, our model exhibited higher discriminative power than did the prediction model developed by Kang et al [ 7 ].…”
Section: Discussionsupporting
confidence: 86%
“…Pattharanitima et al used ML and deep learning to build a model for predicting renal replacement therapy-free survival and demonstrated that the long short-term memory model with multilayer perceptron architecture exhibited high discrimination performance with an AUC of 0.70 [ 13 ]. Studies have investigated the accuracy of other ML-based mortality prediction models in intensive care settings, including in patients with lactic acidosis [ 23 ], mechanically ventilated patients [ 24 ], and those with COVID-19 and AKI [ 25 ]. These findings emphasize the importance of ML in predicting outcomes in critical care settings, especially for patients receiving CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients who died within two weeks of starting MV were excluded from the analysis, leading to a selection bias. Several other studies exist but only predicted mortality 9 and short-term outcomes 10 , or they did not consider death in model building 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The I-TRACH model previously extracted tachycardia, renal dysfunction, acidemia, and a decreased HCO 3 concentration as the main variables for constructing a scoring system 8 . In another study that reported the prediction of 30-day mortality, the essential features in the models were Acute Physiology and Chronic Health Evaluation II score, Charlson Comorbidity Index, use of norepinephrine, and base excess 9 . In our study, lactate level and anion gap were the two most important predictors in the nal VC model.…”
Section: Discussionmentioning
confidence: 99%